Does caring lead to stigmatisation? The perception of older people among healthcare professionals and the general population: A cross‐sectional study. (10th March 2022) - Crutzen, Coline; Missotten, Pierre; Adam, Stéphane; Schroyen, Sarah
Abstract: Background: It is well recognised that healthcare professionals are particularly at risk for developing a negative perception of older people. Indeed, in addition to receiving education centred on a biomedical view of ageing, they are constantly exposed to the most vulnerable and dependent older individuals. Aim: The purpose of our study is to compare the perception of older people between health professionals, working in a nursing home and the general population. Methods: This is a cross‐sectional study. The perception of older people was measured using two different instruments: the image‐of‐ageing question and the Aging Semantic Differential (ASD) scale. We performed t ‐test to compare the perception of older individuals between the general population and healthcare professionals. Results: The image‐of‐ageing question does not show any difference between the general population ( n  = 148) and healthcare professionals ( n  = 107). In these both groups, almost half of the words cited in reference to older individuals were negative. Concerning the ASD, results show that healthcare professionals have significantly more negative perceptions towards older individuals than the general population (with the control of age, gender and educational level). Conclusion: Healthcare professionals seem to have a more negative view of older people than the general population. Their regular contact with the frailest older adults could explain this finding. Another hypothesis could be a non‐optimal quality of contact in nursing homes. Implications for practice: Such results highlight the importance to promote a more holistic view of ageing in educational programs of healthcare professional. Improving the quality of contact with nursing homes residents should be strongly considered to reduce ageism among healthcare professionals.